ANALISIS HARGA DAN KUALITAS PRODUK TERHADAP TINGKAT PENDAPATAN PETANI BAWANG MERAH DI DESA MOJOREMBUN KECAMTAN REJOSO KABUPATEN NGANJUK - Prasetiyo Bayu Aji; Mustafidah Mahardika (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2018)
Revenues are inflows of wealth from the company's activities selling goods and services in a given period, which resulted in the increase of capital which is not derived from the contribution of capital investment.All people of all ages, social status, economic and culture certainly never heard of the word income in indonesia there are quite a lot of termonologi are associated with income.Price and quality plays an important role in communicating increased the income of the farmers in the village, especially red onion Mojorembun, kecamtan Rejoso, Nganjuk Regency. This type of research using the method of causal research is research that is the nature of the causal relationship.In this study the number of samples taken as many as 53 people respondents.The source of the data in this study using questionnaire (question form) and the study of librarianship. The analysis of the data used in the form of multiple linear regression analysis. Testing hypotheses by performing statistical tests t (partial) for testing partially and statistical tests F (simultaneous) for testing simultaneously.Results of the study concluded that the prices and quality of influential simultaneous or partially to increased farmer income of onion in the villages of Mojorembun, Rejoso Sub-district, Nganjuk Regency.